EVALUATION AND MEASUREMENTS OF MAIN FEATURES OF A TABLE TYPE RFID READER - FUJISAKI, KIYOTAKA (Journal of Mobile Multimedia, 2015)
RFID system is one of the key technology to bring efficiency to library services such as the automatic rental of book and return. In this paper, we evaluate the performance of table type RFID reader. Furthermore, when RFID reader is on the metallic plate (which affected the performance of RFID), we investigate the relation between the reading rate and the distance between metallic plate and RFID reader. From the experiments, it is clearly shown that communication area decreases and becomes near the center of reader’s antenna as the distance between the tag and the reader increases. The influence of the metallic plate to the reader depends on the gap between the metallic plate and the reader.